Reklama religijna jako przekaz perswazyjny z elementami sacrum - Stępniak, Krzysztof (Studia Theologica Varsaviensia, 2018)
Religious advertising as a persuasive message with elements of the sacrum - Summary Religious advertising is a particular phenomenon in the reality surrounding us. It is becoming more and more a tool of communication of the Catholic Church used for various purposes; Pastoral, vocation or evangelization. It is often associated with social advertising, although it is not a type of social advertising. It is a type of persuasive message that contains elements of the sacrum, which distinguishes it from other types of ads. In this text, the author presents his own definition of religious advertising, its types and defines its purpose. He also presents a slice of focus studies on the phenomenon of religious advertising and its reception in selected groups in Poland, conducted in 2016. The presentation of own research deals with the problems and doubts that the concept of religious advertising carries, the description of the phenomenon itself, and focuses on the sacrum as the constitutive element of this type of medium.